2011
DOI: 10.2169/internalmedicine.50.4623
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Resistance and the Effect of Combination Cilostazol in Patients with Ischemic Stroke or Carotid Artery Stenting Using the VerifyNow P2Y12 Assay

Abstract: Objective The inhibitory response to clopidogrel considerably varies among individuals and clopidogrel resistance is a risk factor for thrombotic events in patients with cardiovascular disease. Based on the platelet aggregation evaluated by the VerifyNow P2Y12 Assay, the present study investigated clopidogrel resistance and the effect of cilostazol addition. Methods We measured the ability of 20 μM ADP to aggregate platelets using the VerifyNow P2Y12 Assay. Clopidogrel resistance was defined as % inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…The prevalence of aspirin-HTPR on the VerifyNow in this study was similar to other studies in the early phase after stroke [73]. The prevalence of clopidogrel-HTPR was higher than that reported in the early phase after stroke [74], but similar to another study in late phase CVD patients. [37] Jover et al assessed clopidogrel-HTPR in 18 TIA/stroke patients with the VerifyNow P2Y12 assay, INNOVANCE Õ PFA P2Y cartridge, 5 mmol/l ADP-induced optical aggregometry and vasodilatorstimulated phosphoprotein 7 and 90 days after commencing clopidogrel 75 mg daily as monotherapy or in combination with aspirin 100-300 mg daily [77].…”
Section: The Verifynowsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of aspirin-HTPR on the VerifyNow in this study was similar to other studies in the early phase after stroke [73]. The prevalence of clopidogrel-HTPR was higher than that reported in the early phase after stroke [74], but similar to another study in late phase CVD patients. [37] Jover et al assessed clopidogrel-HTPR in 18 TIA/stroke patients with the VerifyNow P2Y12 assay, INNOVANCE Õ PFA P2Y cartridge, 5 mmol/l ADP-induced optical aggregometry and vasodilatorstimulated phosphoprotein 7 and 90 days after commencing clopidogrel 75 mg daily as monotherapy or in combination with aspirin 100-300 mg daily [77].…”
Section: The Verifynowsupporting
confidence: 89%
“…Further studies identified aspirin-HTPR in 21% of patients on 100-200 mg of aspirin monotherapy41 week after TIA/ischaemic stroke onset [73], and clopidogrel-HTPR in 29% on 75 mg of clopidogrel daily within 1 week of TIA/ischaemic stroke with the VerifyNow [74].…”
Section: The Verifynowmentioning
confidence: 99%
“…An abnormal antiplatelet response was defined as Ͼ550 aspirin response units (ARUs) and/or Ͼ240 P2Y12 receptor reaction units (PRUs). 15,16 Also, we tried to investigate and clarify the optimal cutoff values of both ARUs and PRUs that were associated with DPL, which have been controversial in the literature.…”
Section: Antiplatelet Therapy and Antiplatelet Function Testmentioning
confidence: 99%
“…Also, resistance to clopidogrel is a major risk factor for thrombotic events in patients with cardiovascular disease conditions. In a study carried out by Maruyama H. et al, evaluated by the VerifyNow P2Y12 assay, the effect of the addition of cilostazol on clopidogrel resistance was investigated [4]. Of the 72 patients in the study, 15 patients who received 75 mg of clopidogrel in addition to 100/200 mg of cilostazol, platelet inhibition was intensified; thereby suggesting that the addition of cilostazol may proves to be efficious in the treatment of patients with ischemic stroke and other CVD.…”
Section: Fig 1: Structure Of (A) Cilostazol and (B) Clopidogrelmentioning
confidence: 99%